Vloga in pomen uvedbe administracije gradbenih projektov s podporo projektnega portala - Šuman, Nataša (Gradbeni vestnik, 2011)
Construction projects are complex, interdisciplinary, object oriented investment processes. The characteristics of construction industry, such as the fact that every single construction represents huge financial funds, that it has long duration, and that with every building we construct a part of nature, require the needs for an effective expert and social supervision of construction activities. Hence badly designed, constructed and managed projects have a long-term influence on the quality of social development and request additional funding for building maintenance and renovation. For the purpose of setting the effective management of a construction project we suggest the implementation of Construction Project Administration (CPA) in the paper that will ensure quality and successful project realisation. Construction Project Administration is represented as a tool for arranging optimal operation of work and assuring optimal inclusion of project participants. In the paper, the analysis of valid legislation and the practice of a construction project are presented. Some proposals for improvement are given. Special attention is drawn to assert a new project participant named Construction Project Manager. Accor-ding to the given competences, the so called Construction Project Manager could assure appropriate level of project realisation within the CPA. The designing of modified project organisation and the implementation of Project Portal are the most prominent among the suggestions for improvement.
Keywords: gradbeni projekti; investicije